Testicular fluorine-18 fludeoxyglucose uptake on positron emission tomography CT in patients with lymphoma: clinical significance and management impact - Sidhu, P (Br J Radiol, 2014)
OBJECTIVE: This is the first case series examining the role of fluorine-18 fludeoxyglucose ((18)F-FDG) positron emission tomography-CT (PET-CT) in the diagnosis of lymphoma, and its impact on the clinical management of patients with secondary testicular involvement. This study explores the clinical significance of abnormal testicular uptake, maximum standardized uptake values and the diagnostic value of the CT component in PET-CT scans of these patients. METHODS: The case notes and PET scans of 12 patients with diagnosis of lymphoma that were reported to have abnormal (18)F-FDG uptake in the testes were examined. Case notes were reviewed for the underlying diagnosis, indication for the scan and its effect on the management decision. RESULTS: 12 patients demonstrated abnormal (18)F-FDG uptake on the PET-CT scans (mean age, 63 years; range, 37–82 years). Seven patients were diagnosed with testicular lymphoma. Six out of the seven (86%) patients received additional intrathecal chemotherapy in addition to their systemic chemotherapy, and one patient had testicular radiotherapy. CONCLUSION: This study establishes the importance of identifying and reporting abnormal (18)F-FDG uptake in the testes on PET-CT in patients with lymphoma. (18)F-FDG PET-CT is superior to conventional imaging in identifying testicular lymphoma and has significant management impact. It also emphasizes the importance of incorporating the testes as part of the scan coverage. ADVANCES IN KNOWLEDGE: The appearances of testicular lymphoma on (18)F-FDG PET-CT can be variable and abnormal testicular uptake warrants further investigations and confirmation. FDG PET-CT is an important tool and can be used in addition to conventional imaging in the identification of testicular lymphoma.